(untitled) (GYMNASIUM, 2017)
Interpretation of statistical data has become extremely common in the current period in which technology has greatly advanced. In handball, this kind of data is commonly used, coaches and specialists comparing field data obtained at European and global level with their own teams, in order to align with the latest requirements and trends in handball. An interpretation correctly made and converted into realistic conclusions can lead to improvements of all quantitative and qualitative parameters, when speaking about individual or team play. The aim of the research is to compare the statistical parameters of the female wing players from two different countries, Denmark and Romania, with accent on the differences in wing players’ preferences and shooting efficiency for each situation in which the players were found.